Construction of sacrificial bonds and hybrid networks in EPDM rubber towards mechanical performance enhancement - Li, Chengjie; Wang, Yujie; Yuan, Zun; Ye, Lin (Applied surface science, 2019)
Through a facile method in the process of milling/hot pressing of ethylene-propylene-diene monomer (EPDM) rubber in solid state, the hybrid networks formed by covalent crosslinks, hydrogen bonds and Zn2+-carboxyl units were successfully designed and constructed in EPDM rubber system (EPDM-g-ZnGlu) by incorporation of carboxyl groups onto EPDM backbone and coordination with ZnCl2. The dynamic features capable of reversibly breaking and reforming for the sacrificial hydrogen bonds and Zn2+-carboxyl units endowed EPDM-g-ZnGlu with remarkable hysteresis loss, evident residual strain and rapid stress relaxation, which can be preferentially ruptured before breaking of covalent bonds upon deformation, thus resulting in high energy dissipation and significantly enhanced mechanical strength and toughness of EPDM rubber. Compared with EPDM, the mechanical strength and toughness of EPDM-g-ZnGlu-1/1 increased by 288% and 156%, respectively. Meanwhile, the reprocessing ability was imparted to EPDM-g-ZnGlu samples cured by the sacrificial bonds, further confirming the dynamic characteristics of the sacrificial bonds. Such efficient strategy shows a promising perspective in rational design of EPDM rubbers for practical applications in diverse fields. [Display omitted] •Sacrificial bonds and hybrid networks were first constructed in EPDM rubber.•EPDM-g-ZnGlu presented dynamic feature capable of reversibly breaking & reforming.•EPDM-g-ZnGlu gained obvious hysteresis loss, residual strain & stress relaxation.•High energy dissipation and remarkably enhanced mechanical property were achieved.•Reprocessing ability was imparted to EPDM-g-ZnGlu cured by sacrificial bonds.